Network technology and online learning: Towards the creation of world-class university / Azmi Salim - Salim, Azmi (Universiti Teknologi MARA Cawangan Pahang, 2005)
Global concept has developed as fast as the computer technology itself and ICT nowadays is not meant for business purposes only, but also for other IT dependent industries which include "Education". Online-learning is a result of fast evolving networking technology. As networking technology evolved and more communication tools were developed, the online-learning becomes more practical. Collaborative technologies and groupware backed up by a great networking technology are very important in order to realize the aspiration towards a world-class university and be in the mainstream.